TRANSFORMASI PELAYANAN PUBLIK MELALUI E-GOVERNMENT DI MASA ERA NEW NORMAL PADA PEMERINTAH DAERAH BADUNG - Kadek Wiwin Dwi Wismayanti; Putu Eka Purnamaningsih (LPSDI Bina Patria, 2022)
In a pandemic situation in the new normal era with limited community mobility in carrying out daily activities, which aims to break the chain of transmission and spread of the Covid-19 virus, the application of e-government is a solution for the government to be able to provide services to the public. E-government is a government program in an effort to develop electronic-based government administration and carry out transformations to facilitate community and business activities. use of information and communication technology. Utilization and development of telecommunications technology began to be developed in the governance process of the Bali Province, namely in Badung Regency. The location of this research is in the Badung Regency Government Center. This research uses qualitative research with descriptive method. Data collection techniques by means of observation, interviews, questionnaires, literature study and documentation. The informants in this study were the Head of the Badung Regency Communication and Information Office (Diskominfo), the Head of the Badung Regency Investment and One Stop Service (PTSP), the Head of the Regional Revenue Agency, and the Head of the Badung Regency Population and Civil Registration Office. With the implementation of e-government in the government process, the process of providing government services to the community becomes more effective, efficient, and safe, so that it can provide excellent service. The results of this study indicate that E-Government-based public services in Badung Regency have been running well in accordance with the successful elements of E-Government development, namely Support, Capacity, and Value